"I Do Think We Did the Right Things at the Right Time to Generate the Right Buzz1:" A TPC Framework for Public Events. Issue 1 (2nd January 2023) - Silvestro, John J
ABSTRACT: To support collaborations between technical communicators and nonprofits, this article outlines a framework for composing public events. The article develops a technical and professional communication (TPC) lens for public events and then draws that together with a case study of a nonprofit's strategies for their public event. Through this work, the article outlines a framework for organizing and managing public events that can engage challenging publics around complex information.